Clinicopathological analysis of adrenal intravascular large B-cell lymphoma - LIN Jiaxin, WEI Ran, SHUI Ruohong, LU Hongfen, LI Xiaoqiu, YU Baohua (Zhongguo aizheng zazhi)
Background and purpose: Primary adrenal intravascular large B-cell lymphoma (IVLBCL) is rare and highly aggressive. Unfortunately, comprehensive and sufficient understanding of the disease is lacking. This study investigated the clinicopathological and molecular genetic characteristics of adrenal IVLBCL. Methods: Adrenal IVLBCL cases diagnosed from 2012 to 2023 were collected from Department of Pathology, Fudan University Shanghai Cancer Center. The clinical and histopathological features, immunophenotype, treatment and prognosis were analyzed. The molecular genetic characteristics were detected using next-generation sequencing (NGS). This study was approved by the Ethics Committee of Fudan University Shanghai Cancer Center (Ethics number: 050432-4-2307E). Results: All of the 5 patients were male, with median age 52 years (ranged 50-82 years). Two cases had low-grade fever, 1 case had abdominal pain, 1 case was found by physical examination, and the information of the remaining one was unknown. Peripheral blood test showed elevated serum lactate dehydrogenase in 2 cases and adrenal dysfunction in 2 cases. On initial diagnosis, imaging tests displayed adrenal enlargement or masses with increased fluorodeoxyglucose (FDG) uptake. Bilateral adrenal glands were involved in 4 cases and only the right adrenal gland was involved in the other case. Morphologically, large atypical lymphocytes were confined to blood vessels, and fibrinous necrosis was observed in some cases. Immunohistochemical study revealed that CD20 was positive in all cases. Ki-67 proliferation index was high, all above 80%. 80% (4/5) of the cases were of non-germinal-center B-cell-like (non-GCB) phenotype, 100% (4/4) of the cases had MYC/BCL2 double expression. Endothelial cell markers staining indicated that most of the tumor cells were confined within the blood vessels in all cases. Follow-up data were available in 3 patients. One patient who underwent only surgical resection died 5 months after diagnosis, one achieved complete remission after surgery plus R-CHOP, and the other diagnosed by biopsy achieved a partial remission after R-CHOP. The 1-year overall survival rate was 66.7%, and overall survival was 5-87 months. NGS testing in 1 case showed missense mutations in MYD88 V217F, TP53, CDH1, ARID1B, MSH3, MLH3, PTPRK, CD22 and FLCN. Conclusion: Adrenal IVLBCL is rare and tends to occur in the middle-aged and elderly male. The majority of our patients were non-GCB phenotype, often accompanied by MYC/BCL2 double expression, and MYD88 non-L265P mutation was detected. Early diagnosis of adrenal IVLBCL is difficult due to its diverse clinical symptoms and lack of specificity. It is of great importance to accumulate more cases and further understand the clinicopathological and molecular genetic characteristics of this rare disease, which might not only help with early diagnosis, timely treatment and improvement of prognosis, but also provide a theoretical basis for further understanding the pathogenesis and development of the disease and exploring therapeutic targets.